IMPORTATION OF PUMPING EQUIPMENT IN PIPING CO., LTD ABC - ANALYSIS OF PATTERNS AND SOME RECOMMENDATION SOLUTIONS - Hoang, Vo Le; Syahputri, Rahmalia (Prosiding International conference on Information Technology and Business (ICITB), 2018)
Import-export activities have meaningfully and significantly influenced and tributed to every economy. However, the effect and the influent scale of these activities, especially importation, still have not been popularly declared. The objectives of this study are analysing and evaluating the importation of pumps based on the study of common issues in import activities of the company ABC located in Ho Chi Minh city that run a piping business. Besides, this paper overview, through the data obtained, to see the fluctuation of the index in the import activities of the company. Accordingly, strengths, weaknesses, opportunities, and threats of the company ABC are pointed out by the SWOT matrix analysis method. From this, several solutions and recommendations are proposed for optimizing advantages and benefits of import activities of the company ABC in particular and the whole economy of Vietnam in general.Keywords: importation; piping company; solutions and recommendations; SWOT matrix.